The role of the dorsal striatum in choice impulsivity - Kim, BaekSun; Im, Heh-In (New York Academy of Sciences, 2019)
It has long been recognized that the dorsal striatum is an essential brain region for control of action selection based on action-outcome contingency learning, particularly when the available actions are bound to rewarding outcomes. In principle, intertemporal choice in the delay-discounting task-a validated measure of choice impulsivity-involves reward-associated actions that require the recruitment of the dorsal striatum. Here, we conjecture about ways the dorsal striatum is involved in choice impulsivity. Based on a selective body of studies, we begin with a brief history of research on choice impulsivity and the dorsal striatum, and then provide a comprehensive summary of contemporary studies utilizing human neuroimaging and animal models to search for links between choice impulsivity and the dorsal striatum. In particular, we discuss in-depth the converging evidence for the associations of choice impulsivity with the reward valuation coded by the caudate, a ventral-to-dorsal gradient in the dorsal striatum, the origins of striatal afferents, and developmental maturation of frontostriatal connectivity during adolescence.